Acquisition, mobility and food insecurity: integrated food systems opportunities across urbanicity levels highlighted by COVID-19. Issue 1 (25th January 2022) - Mui, Yeeli; Headrick, Gabby; Raja, Samina; Palmer, Anne; Ehsani, Johnathon; Pollack Porter, Keshia
Abstract: Objective: To investigate acquisition and mobility experiences of food-insecure individuals across urbanicity levels (i.e., urban, suburban, rural) in the early months of the COVID-19 pandemic. Design: Cross-sectional study using a nationally representative online panel to measure where food-insecure individuals acquired food, food acquisition barriers and mobility to food sources, which were evaluated across urbanicity levels using chi-squared tests and 95 % CI. Setting: USA. Participants: 2011 adults (18 years or older). Results: Food insecurity impacted 62·3 % of adults in urban areas, 40·5 % in rural areas and 36·7 % in suburban areas ( P < 0·001). Food acquisition barriers that were significantly more prevalent among food-insecure adults in urban areas were a change in employment status (34·2 %; 95 % CI 27·2 %, 41·1 %; P < 0·0001) and limited availability of food in retailers (38·8 %; 95 % CI 31·7 %, 45·9 %; P < 0·001). In rural areas, food-insecure adults primarily acquired food for the household from supercentres (61·5 %; 95 % CI 50·4 %, 72·5 %; P < 0·05), while locally sourced foods were less common among food-insecure adults in rural areas (6·9 %; 95 % CI 0·01 %, 13·0 %) compared to urban areas (19·8 %; 95 % CI 14·3 %, 25·4 %; P < 0·01). Transportation as a barrier did not vary significantly by urbanicity, but food-insecure adults across urbanicity levels reported utilising a range of transportation modes to acquire food. Conclusions: A planning approach that links urban and rural areas could address food insecurity by enhancing the integration of food production, transportation and food distribution, building towards a more resilient and equitable food system for all Americans.